Towards a new conceptualization of Bioethics and application of its principles in the legal system - Diaz Piragauta, Brayan Alexander (Universidad Pedagógica y Tecnológica de Colombia, 2020)
This article aims to show how bioethics has evolved through its application to the field of law. Likewise, to know how the application of bioethical principles to the legal system overcomes the imposition of unique moral codes, which influence decision making to regulate, from the legal field, diverse topics of interest. Some of them are abortion and euthanasia, which, for their development, require a bioethical weightingof rights. Especially in contexts where the need to develop a bioethical application in the democratic societies of the 21st century arises from the legal systems of pioneering countries, based on the participation of autonomous citizens, through deliberative procedures at all institutional and social levels. Under the methodology of analysis and doctrinal, jurisprudential and constitutional synthesis, it is evident how the application of bioethical principles to specific issues of law, results in a significant social responsibility that gives importance to cases and complex legal situations. These are resolved through the weighting of rights, in coherence with the evidence of scientific progress. Having as main result, a synthesis of the relationship between law and bioethics, leading to the importance of a participative and open elaboration of the norms and the implementation of legal answers related to each case.